Day 2 Tue, August 03, 2021 2021
DOI: 10.2118/207167-ms
|View full text |Cite
|
Sign up to set email alerts
|

Production and Performance Evaluation of Biodetergents as an Alternative to Conventional Drilling Detergent

Abstract: Drilling detergents are among the chemical compounds that are increasingly being used in many varieties of drilling fluids. They are aqueous blend of surface-active agents that reduces the surface tension of water-based drilling fluids, reduces the sticking tendency of water-sensitive shale cuttings and aid cuttings removal; leading to cleaner hole, faster penetration rates and lower drilling pressure. Due to the increase in environmental issues associated with the disposal of drilling detergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…These oil extraction yields are comparable to those of Elaeis guineensis oils of 46.8% and 43.2% for palm oil and palm kernel oil respectively. These percentage oil yields are higher than those of plants found in the Niger Delta notably Azadirachta indica seed oil of 38% [103]; Chrysophyllum albidum seed oil of 30.6% [78]; Jatroha curcas seed oil of 42.5% [104]; Hevea brasiliensis (Rubber) seed oil of 43% [105]; Lagenaria siceraria seed oil of 35% [106]; Nicotiana tabacum seed oil of 32.1% [80]; Ricinus communis seed oil of 42% [103]. These results showed that just like the Elaeis guineensis, the common species of the Niger Delta Raphia Palm fruits are prolific in oil.…”
Section: Oil Yieldmentioning
confidence: 64%
See 3 more Smart Citations
“…These oil extraction yields are comparable to those of Elaeis guineensis oils of 46.8% and 43.2% for palm oil and palm kernel oil respectively. These percentage oil yields are higher than those of plants found in the Niger Delta notably Azadirachta indica seed oil of 38% [103]; Chrysophyllum albidum seed oil of 30.6% [78]; Jatroha curcas seed oil of 42.5% [104]; Hevea brasiliensis (Rubber) seed oil of 43% [105]; Lagenaria siceraria seed oil of 35% [106]; Nicotiana tabacum seed oil of 32.1% [80]; Ricinus communis seed oil of 42% [103]. These results showed that just like the Elaeis guineensis, the common species of the Niger Delta Raphia Palm fruits are prolific in oil.…”
Section: Oil Yieldmentioning
confidence: 64%
“…Oils with iodine value above 150 are classified as drying oils; those with iodine value 125 -150 are classified as semidrying oils and those with iodine value less than 125 are considered as nondrying oil. Oil with low Iodine numbers (saturated oils) are well suited for soap/ detergent production [103,130,131]. Oils/fats with low iodine values are also well suited for wafer baking [132].…”
Section: Iodine Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most realistic alternative is based on the regulation and use of biodetergents that biodegrade in water after a certain time. However, it must be highlighted that until they do, many bio-detergents are still harmful substances [7,8].…”
Section: Introductionmentioning
confidence: 99%